Marcelin Defourneaux, Pablo Olavide ou l'afrancesado (1725-1823). Presses Universitaires de France, Paris, 1959; 500 pp. - Zavala, Iris M. (Nueva Revista de Filología Hispánica (NRFH), 1964)
Se reseñó el libro: Pablo Olavide ou l'afrancesado (1725-1823).